Against Ryan Byerly: In defense of the actual world formulation of the argument for atheism - Camesa, Sean Bailey P. (Animo Repository, 2022)
In ‘Ordinary Morality Does Not Imply Atheism,’ Ryan Byerly presents several criticisms against claim two of the actual world formulation of the argument for atheism which asserts that if all actual instances of undeserved, unwanted suffering produce a net benefit for the sufferer, then the moral obligations of human persons are not as ordinary morality dictates. He argues that these criticisms are sufficient grounds for rendering the claim 'highly questionable.' This paper argues that Byerly’s criticisms are mistaken and concludes that claim two is, at the very least, not highly questionable. This paper attempts to show that (i) instances of suffering and injustices which lead to beneficial consequences will still have beneficial consequences that outweigh ‘disastrous consequences’ even when performed en masse, thus retaining its ‘morally right’ status, (ii) there will be absolutely no obligation to prevent evil if theodical individualism, i.e., claim 2, were to be true and real, and that (iii) failing to prevent evil under theodical individualism does not, and will not result in overall destruction. Furthermore, this paper suggests that the actual world formulation, having escaped Byerly’s criticisms, is still worthy of being employed as a viable resource for discourse against a morally perfect God.